Application of cyclic phosphonamide reagents in the total synthesis of natural products and biologically active molecules - Focken, Thilo; Hanessian, Stephen (Beilstein Journal of Organic Chemistry, 2014)
A review of the synthesis of natural products and bioactive compounds adopting phosphonamide anion technology is presented highlighting the utility of phosphonamide reagents in stereocontrolled bond-forming reactions. Methodologies utilizing phosphonamide anions in asymmetric alkylations, Michael additions, olefinations, and cyclopropanations will be summarized, as well as an overview of the synthesis of the employed phosphonamide reagents.
Keywords: conjugate addition; cyclopropanation; olefination; organophosphorus; phosphonamide; total synthesis

(untitled) - Hanessian, S.; Delorme, D.; Beaudoin, S.; Leblanc, Y. (J. Am. Chem. Soc., 1984)

(untitled) - Denmark, S. E.; Kim, J.-H. (J. Org. Chem., 1995)

(untitled) - Denmark, S. E.; Chen, C.-T. (J. Am. Chem. Soc., 1995)

(untitled) - Denmark, S. E.; Kim, J.-H. (Can. J. Chem., 2000)

(untitled) - Hua, D. H.; Can-Yu-King, R.; McKie, J. A.; Myer, L. (J. Am. Chem. Soc., 1987)

(untitled) - Hua, D. H.; Chen, J. S.; Sha, S.; Wang, H.; Roche, D.; Bharathi, S. N.; Chan-Yu-King, R.; Robinson, P. D.; Iguchi, S. (Synlett, 1992)

(untitled) - Sting, M.; Steglich, W. (Synthesis, 1990)

(untitled) - Giovenzana, G. B.; Pagliarin, R.; Palmisano, G.; Pilati, T.; Sisti, M. (Tetrahedron: Asymmetry, 1999)

(untitled) - Cravotto, G.; Giovenzana, G. B.; Pagliarin, R.; Palmisano, G.; Sisti, M. (Synth. Commun., 2001)

(untitled) - Hanessian, S. (J. Org. Chem., 2012)

(untitled) - Denmark, S. E.; Stadler, H.; Dorow, R. L.; Kim, J.-H. (J. Org. Chem., 1991)

(untitled) - Denmark, S. E.; Marlin, J. E.; Rajendra, G. (J. Org. Chem., 2013)

(untitled) - Molt, O.; Schrader, T. (Synthesis, 2002)

(untitled) - Bennani, Y. L.; Hanessian, S. (Chem. Rev., 1997)
See for a review.

(untitled) - Corey, E. J.; Cane, D. E. (J. Org. Chem., 1969)

(untitled) - Patois, C.; Savignac, P. (Tetrahedron Lett., 1991)

(untitled) - Patois, C.; Savignac, P. (Synlett, 1991)

(untitled) - Hanessian, S.; Bennani, Y. L.; Leblanc, Y. (Heterocycles, 1993)

(untitled) - Corey, E. J.; Kwiatkowsky, G. T. (J. Am. Chem. Soc., 1968)

(untitled) - McMurry, J. E.; von Beroldingen, L. A. (Tetrahedron, 1974)

(untitled) - Denmark, S. E.; Amburgey, J. (J. Am. Chem. Soc., 1993)

(untitled) - Hanessian, S.; Beaudoin, S. (Tetrahedron Lett., 1992)

(untitled) - Hanessian, S.; Beaudoin, S. (Tetrahedron Lett., 1992)

(untitled) - Hanessian, S.; Fu, J.-M.; Tu, Y.; Isono, K. (Tetrahedron Lett., 1993)

(untitled) - Hanessian, S.; Fu, J.-M.; Chiara, J.-L.; Di Fabio, R. (Tetrahedron Lett., 1993)

(untitled) - Hanessian, S.; Fu, J.-m. (Can. J. Chem., 2001)

(untitled) - Hanessian, S.; Focken, T.; Oza, R. (Org. Lett., 2010)

(untitled) - Hanessian, S.; Focken, T.; Mi, X.; Oza, R.; Chen, B.; Ritson, D.; Beaudegnies, R. (J. Org. Chem., 2010)

(untitled) - Hanessian, S.; Bennani, Y. L.; Delorme, D. (Tetrahedron Lett., 1990)

(untitled) - Bennani, Y. L.; Hanessian, S. (Tetrahedron, 1996)

(untitled) - Hanessian, S.; Bennani, Y. L. (Tetrahedron Lett., 1990)

Aminophosphonic and Aminophosphinic Acids: Chemistry and Biological Activity - Kukhar, V. P.; Hudson, H. R. (John Wiley & Sons, 2000)

(untitled) - Ma, J.-A. (Chem. Soc. Rev., 2006)

(untitled) - Naydenova, E. D.; Todorov, P. T.; Troev, K. D. (Amino Acids, 2010)

(untitled) - Hanessian, S.; Bennani, Y. L. (Synthesis, 1994)

(untitled) - Lawrence, R. M.; Biller, S. A.; Dickson, J. K., Jr; Logan, J. V. H.; Magnin, D. R.; Sulsky, R. B.; DiMarco, J. D.; Gougoutas, J. Z.; Beyer, B. D.; Taylor, S. C.; Lan, S.-J.; Ciosek, C. P., Jr; et al. (J. Am. Chem. Soc., 1996)

(untitled) - Hanessian, S.; Gomtsyan, A.; Payne, A.; Hervé, Y.; Beaudoin, S. (J. Org. Chem., 1993)

(untitled) - Hanessian, S.; Gomtsyan, A. (Tetrahedron Lett., 1994)

(untitled) - Hanessian, S.; Gomtsyan, A.; Malek, N. (J. Org. Chem., 2000)

(untitled) - Hanessian, S.; Griffin, A. M.; Cantin, L.-D. (Chirality, 2000)

(untitled) - Paquette, L. A.; Wang, T.-Z.; Pinard, E. (J. Am. Chem. Soc., 1995)

(untitled) - Wang, T.-Z.; Pinard, E.; Paquette, L. A. (J. Am. Chem. Soc., 1996)

(untitled) - Wu, X.; Zhou, J.; Snider, B. B. (Angew. Chem., Int. Ed., 2009)

(untitled) - Foucher, V.; Guizzardi, B.; Groen, M. B.; Light, M.; Linclau, B. (Org. Lett., 2010)

(untitled) - Boyle, C. D.; Kishi, Y. (Tetrahedron Lett., 1995)

(untitled) - Shi, Y.; Peng, L. F.; Kishi, Y. (J. Org. Chem., 1997)

(untitled) - Hartl, M.; Humpf, H.-U. (J. Org. Chem., 2001)

(untitled) - Hailes, H. C.; Isaac, B.; Javaid, M. H. (Tetrahedron Lett., 2001)

(untitled) - Hanessian, S.; Mainetti, E.; Lecomte, F. (Org. Lett., 2006)

(untitled) - Xiao, Q.; Jackson, J. J.; Basak, A.; Bowler, J. M.; Miller, B. G.; Zakarian, A. (Nat. Chem., 2013)

(untitled) - Hanessian, S.; Andreotti, D.; Gomtsyan, A. (J. Am. Chem. Soc., 1995)

(untitled) - Reissig, H.-U. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Donaldson, W. A. (Tetrahedron, 2001)

(untitled) - Lebel, H.; Marcoux, J.-F.; Molinaro, C.; Charette, A. B. (Chem. Rev., 2003)

(untitled) - Chen, D. Y.-K.; Pouwer, R. H.; Richard, J.-A. (Chem. Soc. Rev., 2012)

(untitled) - Hanessian, S.; Cantin, L.-D.; Andreotti, D. (J. Org. Chem., 1999)

(untitled) - Marinozzi, M.; Pellicciari, R. (Tetrahedron Lett., 2000)

(untitled) - Clive, D. L. J.; Liu, D. (J. Org. Chem., 2008)

(untitled) - Hanessian, S.; Cantin, L.-D.; Roy, S.; Andreotti, D.; Gomtsyan, A. (Tetrahedron Lett., 1997)

(untitled) - Marinozzi, M.; Serpi, M.; Amori, L.; Diaz, M. G.; Costantino, G.; Meyer, U.; Flor, P. J.; Gasparini, F.; Heckendorn, R.; Kuhn, R.; Giorgi, G.; Hermit, M. B.; et al. (Bioorg. Med. Chem., 2007)

(untitled) - Amori, L.; Serpi, M.; Marinozzi, M.; Costantino, G.; Diaz, M. G.; Hermit, M. B.; Thomsen, C.; Pellicciari, R. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Hanessian, S.; Cantin, L.-D. (Tetrahedron Lett., 2000)

(untitled) - Hanessian, S.; Moitessier, N.; Cantin, L.-D. (Tetrahedron, 2001)

(untitled) - Hanessian, S.; Bennani, Y. L.; Hervé, Y. (Synlett, 1993)

(untitled) - Stowell, M. H. B.; Ueland, J. M.; McClard, R. W. (Tetrahedron Lett., 1990)

(untitled) - Rogers, R. S. (Tetrahedron Lett., 1992)

(untitled) - Kinnear, A. M.; Perren, E. A. (J. Chem. Soc., 1952)
See for the synthesis of allylphosphonic acid dichloride.

(untitled) - Kotoris, C. C.; Wen, W.; Lough, A.; Taylor, S. D. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Koeller, K. J.; Spilling, C. D. (Tetrahedron Lett., 1991)

(untitled) - Blazis, V. J.; Koeller, K. J.; Spilling, C. D. (Tetrahedron: Asymmetry, 1994)

(untitled) - Blazis, V. J.; Koeller, K. J.; Spilling, C. D. (J. Org. Chem., 1995)

(untitled) - Isono, K.; Asabi, K.; Suzuki, S. (J. Am. Chem. Soc., 1969)
And references cited therein.

(untitled) - Emmer, G. (Tetrahedron, 1992)
See for a synthesis of the racemic unnatural (E)-polyoximic acid.

(untitled) - Sun, H. H.; McEnroe, F. J.; Fenical, W. (J. Org. Chem., 1983)

(untitled) - Midland, S. L.; Wing, R. M.; Sims, J. J. (J. Org. Chem., 1983)

(untitled) - Menys, V. C.; Durrington, P. N. (Br. J. Pharmacol., 2003)

(untitled) - Kourounakis, A. P.; Katselou, M. G.; Matralis, A. N.; Ladopoulou, E. M.; Bavavea, E. (Curr. Med. Chem., 2011)

(untitled) - Do, R.; Kiss, R. S.; Gaudet, D.; Engert, J. C. (Clin. Genet., 2009)

(untitled) - Bezuidenhout, S. C.; Gelderblom, W. C. A.; Gorst-Allman, C. P.; Horak, R. M.; Marasas, W. F. O.; Spiteller, G.; Vleggaar, R. (J. Chem. Soc., Chem. Commun., 1988)

(untitled) - Gelderblom, W. C.; Jaskiewicz, K.; Marasas, W. F.; Thiel, P. G.; Horak, R. M.; Vleggaar, R.; Kriek, N. P. (Appl. Environ. Microbiol., 1988)

(untitled) - Gelderblom, W. C. A.; Marasas, W. F. O.; Vleggaar, R.; Thiel, P. G.; Cawood, M. E. (Mycopathologia, 1992)

(untitled) - Scott, P. M. (Int. J. Food Microbiol., 1993)

(untitled) - Scott, P. M. (Food Addit. Contam., Part A, 2012)

(untitled) - Pereira, C. L.; Chen, Y.-H.; McDonald, F. E. (J. Am. Chem. Soc., 2009)
See for the total synthesis of fumonisin B1.

(untitled) - Fisher, J. F.; Meroueh, S. O.; Mobashery, S. (Chem. Rev., 2005)

(untitled) - Drawz, S. M.; Bonomo, R. A. (Clin. Microbiol. Rev., 2010)

(untitled) - Worthington, R. J.; Melander, C. (J. Org. Chem., 2013)
And references cited therein.

(untitled) - El-Gamal, M. I.; Oh, C.-H. (Curr. Top. Med. Chem., 2010)

(untitled) - Papp-Wallace, K. M.; Endimiani, A.; Taracila, M. A.; Bonomo, R. A. (Antimicrob. Agents Chemother., 2011)

(untitled) - McKenna, M. (Nature, 2013)

(untitled) - Lewis, K. (Nat. Rev. Drug Discovery, 2013)

(untitled) - Sader, H. S.; Gales, A. C. (Drugs, 2001)

Recent Advances in the Chemistry of Anti-infective Agents - Perboni, S.; Tamburini, B.; Rossi, T.; Donati, D.; Tarzia, G.; Gaviraghi, G. (The Royal Society of Chemistry, T. Graham House, 1992)

(untitled) - Hanessian, S.; Reddy, G. B. (Bioorg. Med. Chem. Lett., 1994)

(untitled) - Hanessian, S.; Rozema, M. J.; Reddy, G. B.; Braganza, J. F. (Bioorg. Med. Chem. Lett., 1995)

(untitled) - Hanessian, S.; Rozema, M. J. (J. Am. Chem. Soc., 1996)

(untitled) - Hanessian, S.; Griffin, A. M.; Rozema, M. J. (Bioorg. Med. Chem. Lett., 1997)

(untitled) - Zheng, G.-C.; Hatano, M.; Ishitsuka, M. O.; Kusumi, T.; Kakisawa, H. (Tetrahedron Lett., 1990)

(untitled) - Zheng, G.-C.; Ichikawa, A.; Ishitsuka, M. O.; Kusumi, T.; Yamamoto, H.; Kakisawa, H. (J. Org. Chem., 1990)

(untitled) - Kende, A. S.; Mendoza, J. S. (Tetrahedron Lett., 1990)

(untitled) - Blakemore, P. R. (J. Chem. Soc., Perkin Trans. 1, 2002)

Modern Carbonyl Olefination - Dumeunier, R.; Markó, I. E. (The Julia Reaction, 2004)

(untitled) - McMurry, J. E.; Bosch, G. K. (J. Org. Chem., 1987)

(untitled) - Ihara, M.; Taniguchi, T.; Tokunaga, Y.; Fukumoto, K. (J. Org. Chem., 1994)

(untitled) - Zhang, Z.-Y. (Annu. Rev. Pharmacol. Toxicol., 2002)

(untitled) - Tonks, N. K. (Nat. Rev. Mol. Cell Biol., 2006)

Foye’s Principles of Medicinal Chemistry - Zato, S. W. (Insulin and drugs used to treat diabetes, 2013)

(untitled) - Rotella, D. P. (J. Med. Chem., 2004)

(untitled) - van Huijsduijnen, R. H.; Sauer, W. H. B.; Bombrun, A.; Swinnen, D. (J. Med. Chem., 2004)

(untitled) - Barr, A. J. (Future Med. Chem., 2010)

(untitled) - Burke, T. R., Jr (Curr. Top. Med. Chem., 2006)

(untitled) - Birkedal-Hansen, H.; Moore, W. G. I.; Bodden, M. K.; Windsor, L. J.; Birkedal-Hansen, B.; DeCarlo, A.; Engler, J. A. (Crit. Rev. Oral Biol. Med., 1993)

(untitled) - Nagase, H.; Visse, R.; Murphy, G. (Cardiovasc. Res., 2006)

(untitled) - Cheong, J.-J.; Choi, Y. D. (Trends Genet., 2003)

(untitled) - Büchi, G.; Egger, B. (J. Org. Chem., 1971)

(untitled) - Tanahashi, T.; Takenaka, Y.; Nagakura, N.; Nishi, T. (Chem. Pharm. Bull., 2000)
And references cited therein.

(untitled) - Tanahashi, T.; Takenaka, Y.; Nagakura, N.; Nishi, T. (J. Nat. Prod., 1999)

(untitled) - Takenaka, Y.; Tanahashi, H.; Taguchi, H.; Nagakura, N.; Nishi, T. (Chem. Pharm. Bull., 2002)

(untitled) - Dhimitruka, I.; SantaLucia, J., Jr (Org. Lett., 2006)

(untitled) - Inanaga, J.; Hirata, K.; Saeki, H.; Katsuki, T.; Yamaguchi, M. (Bull. Chem. Soc. Jpn., 1979)

(untitled) - Niswender, C. N.; Conn, P. J. (Annu. Rev. Pharmacol. Toxicol., 2010)

(untitled) - Amalric, M.; Lopez, S.; Goudet, C.; Fisone, G.; Battaglia, G.; Nicoletti, F.; Pin, J.-P.; Acher, F. C. (Neuropharmacology, 2013)

(untitled) - Attwell, P. J. E.; Kent, N. S.; Jane, D. E.; Croucher, M. J.; Bradford, H. F. (Brain Res., 1998)

(untitled) - Pellicciari, R.; Marinozzi, M.; Natalini, B.; Costantino, G.; Luneia, R.; Giorgi, G.; Moroni, F.; Thomsen, C. (J. Med. Chem., 1996)

(untitled) - Stierle, A. A.; Stierle, D. B.; Kelly, K. (J. Org. Chem., 2006)

(untitled) - McLeod, M. C.; Wilson, Z. E.; Brimble, M. A. (J. Org. Chem., 2012)

(untitled) - Fañanás, F. J.; Mendoza, A.; Arto, T.; Temelli, B.; Rodriguez, F. (Angew. Chem., Int. Ed., 2012)

(untitled) - Wenderski, T. A.; Marsini, M. A.; Pettus, T. R. R. (Org. Lett., 2011)

(untitled) - McLeod, M. C.; Wilson, Z. E.; Brimble, M. A. (Org. Lett., 2011)

(untitled) - Snaddon, T. N.; Buchgraber, P.; Schulthoff, S.; Wirtz, C.; Mynott, R.; Fürstner, A. (Chem.–Eur. J., 2010)

(untitled) - Bender, C. F.; Yoshimoto, F. K.; Paradise, C. L.; De Brabander, J. K. (J. Am. Chem. Soc., 2009)

(untitled) - Buchgraber, P.; Snaddon, T. N.; Wirtz, C.; Mynott, R.; Goddard, R.; Fürstner, A. (Angew. Chem., Int. Ed., 2008)

PCT Int. Appl. - Reichenbach, H.; Höfle, G.; Gerth, K.; Washausen, P. (1997)

(untitled) - Gerth, K.; Washausen, P.; Höfle, G.; Irschik, H.; Reichenbach, H. (J. Antibiot., 1996)

(untitled) - Connor, D. T.; Greenough, R. C.; von Strandtmann, M. (J. Org. Chem., 1977)

(untitled) - Ringel, S. M.; Greenough, R. C.; Roemer, S.; Connor, D.; Gutt, A. L.; Blair, B.; Kanter, G.; von Strandmann, M. (J. Antibiot., 1977)

(untitled) - Höfle, G.; Steinmetz, H.; Gerth, K.; Reichenbach, H. (Liebigs Ann. Chem., 1991)

(untitled) - Wenzel, S. C.; Müller, R. (Nat. Prod. Rep., 2007)

(untitled) - Julien, B.; Tian, Z.-Q.; Reid, R.; Reeves, C. D. (Chem. Biol., 2006)

(untitled) - Michelet, V.; Genêt, J.-P. (Curr. Org. Chem., 2005)
See for a review on ambruticin.

(untitled) - Hanessian, S.; Focken, T.; Oza, R. (Tetrahedron, 2011)

(untitled) - Lee, E.; Choi, S. J.; Kim, H.; Han, H. O.; Kim, Y. K.; Min, S. J.; Son, S. H.; Lim, S. M.; Jang, W. S. (Angew. Chem., Int. Ed., 2002)

(untitled) - Pospíšil, J.; Markó, I. E. (J. Am. Chem. Soc., 2007)
See for the total synthesis of the related jerangolid D.

(untitled) - Pospíšil, J.; Markó, I. E. (Tetrahedron Lett., 2008)

(untitled) - Ohira, S. (Synth. Commun., 1989)

(untitled) - Müller, S.; Liepold, B.; Roth, G. J.; Bestmann, H. J. (Synlett, 1996)

(untitled) - Liu, P.; Jacobsen, E. N. (J. Am. Chem. Soc., 2001)

(untitled) - Kende, A. S.; Fujii, Y.; Mendoza, J. S. (J. Am. Chem. Soc., 1990)

(untitled) - Kende, A. S.; Mendoza, J. S.; Fujii, Y. (Tetrahedron, 1993)

(untitled) - Kirkland, T. A.; Colucci, J.; Geraci, L. S.; Marx, M. A.; Schneider, M.; Kaelin, D. E., Jr; Martin, S. F. (J. Am. Chem. Soc., 2001)

(untitled) - Berberich, S. M.; Cherney, R. J.; Colucci, J.; Courillon, C.; Geraci, L. S.; Kirkland, T. A.; Marx, M. A.; Schneider, M. F.; Martin, S. F. (Tetrahedron, 2003)

National Center for Biotechnology Information. PubChem Compound Database; CID=5870

(untitled) - Chapelon, A.-S.; Moraléda, D.; Rodriguez, R.; Ollivier, C.; Santelli, M. (Tetrahedron, 2007)

(untitled) - Hanson, J. R. (Nat. Prod. Rep., 2010)

(untitled) - Hu, Q.-Y.; Rege, P. D.; Corey, E. J. (J. Am. Chem. Soc., 2004)

(untitled) - Pattenden, G.; Gonzalez, M. A.; McCulloch, S.; Walter, A.; Woodhead, S. J. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Cai, Z. Y.; Covey, D. F. (Steroids, 2007)

(untitled) - Yeung, Y.-Y.; Chein, R.-J.; Corey, E. J. (J. Am. Chem. Soc., 2007)

(untitled) - Hakuba, H.; Kitagaki, S.; Mukai, C. (Tetrahedron, 2007)

(untitled) - Soorukam, D.; Knochel, P. (Org. Lett., 2007)

(untitled) - Canales, E.; Corey, E. J. (Org. Lett., 2008)

(untitled) - Herrmann, P.; Buděšinský, M.; Kotora, M. (J. Org. Chem., 2008)

(untitled) - Xue, Y.-P.; Li, W.-D. Z. (J. Org. Chem., 2011)

(untitled) - Dietz, C.; Jouikov, V.; Jurkshat, K. (Organometallics, 2013)

(untitled) - Hanessian, S.; Leblanc, Y.; Lavallée, P. (Tetrahedron Lett., 1982)

(untitled) - Chauvin, A.-S.; Alexakis, A. (Beilstein J. Org. Chem., 2006)

(untitled) - Mastranzo, V. M.; Quintero, L.; de Parrodi, C. A. (Chirality, 2007)